THE EFFECT OF USING E-MARKETING TOOLS IN ACTIVATING SALES IN HOTELS: A FIELD STUDY IN FIVE-STAR HOTELS IN THE JORDANIAN CAPITAL – AMMAN - Abu Rokbeh, Alanoud Amer Saleem (International Journal of Research -GRANTHAALAYAH, 2022)
The purpose of this study is to look at the effect of employing E-Marketing techniques on activating sales in Amman city hotels. The quantitative technique was utilized in the investigation, with data collected using questionnaires. (500) questionnaires were delivered to guests at (13) Jordanian five-star hotels in Amman. (484) of the (500) questionnaires were recovered, while (16) were eliminated due to excessive missing data. According to the study, adopting E-Marketing tools such as: (the hotel website, hotel blog, hotel social media, and hotel e-mail) has a substantial influence on sales promotion such as: (trade contest, coupons, and rebates). Finally, the study suggests that hotels in Amman continue to implement an E-Marketing policy, activate trade promotion electronically, and promote their services through all electronic channels, particularly social media sites.